Characterization of the Ca2+-gated and voltage-dependent K+-channel Slo-1 of nematodes and its interaction with emodepside. - Daniel Kulke; Georg von Samson-Himmelstjerna; Sandra M Miltsch; Adrian J Wolstenholme; Aaron R Jex; Robin B Gasser; Cristina Ballesteros; Timothy G Geary; Jennifer Keiser; Simon Townson; Achim Harder; Jürgen Krücken (PLoS Neglected Tropical Diseases, 2014)
The cyclooctadepsipeptide emodepside and its parent compound PF1022A are broad-spectrum nematicidal drugs which are able to eliminate nematodes resistant to other anthelmintics. The mode of action of cyclooctadepsipeptides is only partially understood, but involves the latrophilin Lat-1 receptor and the voltage- and calcium-activated potassium channel Slo-1. Genetic evidence suggests that emodepside exerts its anthelmintic activity predominantly through Slo-1. Indeed, slo-1 deficient Caenorhabditis elegans strains are completely emodepside resistant. However, direct effects of emodepside on Slo-1 have not been reported and these channels have only been characterized for C. elegans and related Strongylida. Molecular and bioinformatic analyses identified full-length Slo-1 cDNAs of Ascaris suum, Parascaris equorum, Toxocara canis, Dirofilaria immitis, Brugia malayi, Onchocerca gutturosa and Strongyloides ratti. Two paralogs were identified in the trichocephalids Trichuris muris, Trichuris suis and Trichinella spiralis. Several splice variants encoding truncated channels were identified in Trichuris spp. Slo-1 channels of trichocephalids form a monophyletic group, showing that duplication occurred after the divergence of Enoplea and Chromadorea. To explore the function of a representative protein, C. elegans Slo-1a was expressed in Xenopus laevis oocytes and studied in electrophysiological (voltage-clamp) experiments. Incubation of oocytes with 1-10 µM emodepside caused significantly increased currents over a wide range of step potentials in the absence of experimentally increased intracellular Ca2+, suggesting that emodepside directly opens C. elegans Slo-1a. Emodepside wash-out did not reverse the effect and the Slo-1 inhibitor verruculogen was only effective when applied before, but not after, emodepside. The identification of several splice variants and paralogs in some parasitic nematodes suggests that there are substantial differences in channel properties among species. Most importantly, this study showed for the first time that emodepside directly opens a Slo-1 channel, significantly improving the understanding of the mode of action of this drug class.